ANALYSIS OF APPLICATION OF TECHNIQUE FOR ORDER PREFERENCE BY SIMILLARITY TO IDEAL SOLUTION IN SELECTING ENERGY SAVE ELECTRICAL LIGHTS BALL FOR HOUSEHOLD: ANALYSIS OF APPLICATION OF TECHNIQUE FOR ORDER PREFERENCE BY SIMILLARITY TO IDEAL SOLUTION IN SELECTING ENERGY SAVE ELECTRICAL LIGHTS BALL FOR HOUSEHOLD - Simangunsong, Agustina (Institute of Computer Science (IOCS), 2020)
In this bulb selection of users is often confused with the selection of bulbs that are so much circulating in the market, ranging in terms of brand, type, quality, competitive price and with other advantages that in offer often make the users confused to get a light bulb that is energy efficient at an affordable price and with the best quality. Problems not only stop at the time when the bulb placement in each room of the house also often gets a problem. A common problem is inconsistency, which is common when a light bulb has been placed. Watt capacity available in bulb often does not correspond to the size of the room, resulting in less optimal illumination, watt capacity or large power consumption sometimes also does not guarantee to be able to get a good illumination. Therefore it takes a decision support system that can do the calculation of value to be able to help the user determine the bulb that is desired well and precisely according to the needs. This decision support system implements the method of technique for order preference by Simillarity to ideal solution (TOPSIS), which is a method that can provide a weighted and straddles for each of its criteria. With the technique for order preference by Simillarity to ideal solution (TOPSIS) This author creates a system that hopefully can help the decision making in the selection of electric light bulb. Therefore, the authors feel the need for a decision support system to solve the problem of electric bulb selection for the household.